Dietary Total Fat Intake and Ischemic Stroke Risk: The Northern Manhattan Study - Boden-Albala, Bernadette (S. Karger AG, 2009)
BACKGROUND: Dietary fat intake is associated with coronary heart disease risk, but the relationship between fat intake and ischemic stroke risk remains unclear. We hypothesized that total dietary fat as part of a Western diet is associated with increased risk of ischemic stroke. METHODS: As part of the prospective Northern Manhattan Study, 3,183 stroke-free community residents over 40 years of age underwent evaluation of their medical history and had their diet assessed by a food-frequency survey. Cox proportional hazard models calculated risk of incident ischemic stroke. RESULTS: The mean age of participants was 69 years, 63% were women, 21% were white, 24% black and 52% Hispanic. During a mean of 5.5 years of follow-up, 142 ischemic strokes occurred. After adjusting for potential confounders, risk of ischemic stroke was higher in the upper quintile of total fat intake compared to the lowest quintile (HR 1.6, 95% CI 1.0–2.7). Total fat intake >65 g was associated with increased risk of ischemic stroke (HR 1.6, 95% CI 1.2–2.3). Risk was attenuated after controlling for caloric intake. CONCLUSIONS: The results suggest that increased daily total fat intake, especially above 65 g, significantly increases risk of ischemic stroke.